2012
DOI: 10.5005/jp-journals-10024-1224
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Different Bleaching Agents on the Morphology of Human Enamel: An in vitro SEM Study

Abstract: The purpose of the study was to compare two different commercial bleaching agents, Opalescence with Colgate Platinum, and 30% phosphoric acid used as aggressive agent on the morphology of human enamel. Materials and methods:Ten freshly extracted, noncarious, human maxillary central incisors extracted for periodontal reasons were used in this study. The labial surface of the disinfected teeth were polished using a polishing paste with the help of rubber cup and a slow speed handpiece. Each tooth was sectioned a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
1
3
1
Order By: Relevance
“…As expected, the subgroups 1b (enamel + Perfect Bleach Office+) and 2b (enamel + Perfect Bleach) showed that the bleaching agents cause changes on the enamel structure with a reduction of the hardness number, especially using the professional whitening agent at 35% hydrogen peroxide which was obviously more aggressive than the home whitening at 16% carbamide peroxide (which corresponds to 6% hydrogen peroxide). According to the literature, this study undoubtedly confirmed that teeth whitening procedures led to enamel alterations [49][50][51]. In particular, the oxide-reduction of the peroxides seems to be related to demineralization and dissolution of the organic dental matrix (protein) [5,16,52]; although the organic component represents a minor part of the enamel structure (1%), its action is essential for its integrity since it glues the mineral crystals of the enamel together, preventing micro-hardness loss [53].…”
Section: Discussionsupporting
confidence: 77%
“…As expected, the subgroups 1b (enamel + Perfect Bleach Office+) and 2b (enamel + Perfect Bleach) showed that the bleaching agents cause changes on the enamel structure with a reduction of the hardness number, especially using the professional whitening agent at 35% hydrogen peroxide which was obviously more aggressive than the home whitening at 16% carbamide peroxide (which corresponds to 6% hydrogen peroxide). According to the literature, this study undoubtedly confirmed that teeth whitening procedures led to enamel alterations [49][50][51]. In particular, the oxide-reduction of the peroxides seems to be related to demineralization and dissolution of the organic dental matrix (protein) [5,16,52]; although the organic component represents a minor part of the enamel structure (1%), its action is essential for its integrity since it glues the mineral crystals of the enamel together, preventing micro-hardness loss [53].…”
Section: Discussionsupporting
confidence: 77%
“…In contrast to the results of the present study, Uthappa et al, 32 Engle et al, 33 Faraoni-Romano et al, 34 Basting et al, 35 Cobankara et al 36 and Nucci et al 37 reported, by using SEM analysis, no morphological changes in the enamel surface after the application of 10% carbamide peroxide bleaching. Fatima 38 reported mild changes in surface micro-morphology of enamel, likewise Titley et al 39 observed a slight increase in surface roughness, whereas Gurgan et al 40 reported no modification of surface roughness.…”
Section: Discussioncontrasting
confidence: 94%
“…An explanation might be that lower concentrations of HP, due to the longer exposure time, resulted in similar whitening effects like the products with higher concentration. High concentrated HP whitening products have been well investigated regarding enamel damage (Uthappa et al, 2012; Coceska et al, 2016), also have different remineralization methods (Kemaloglu et al, 2014; Coceska et al, 2016). However, in the present study most notably the pH, ranging from 5.0 to 8.5, and the exposure time seem to influence enamel surface morphology.…”
Section: Discussionmentioning
confidence: 99%